Taman Baca Masyarakat “Tholabul’ilmi” Sebagai Sarana Meningkatkan Literasi Desa Panduman Kecamatan Jelbuk - Menik Chumaidah; Abdul Jalil; Cahya Tribagus Hidayat (Indonesian Journal Publisher, 2020)
Literacy is the ability to access, understand, and use something intelligently through various activities, including reading, listening, writing and speaking. The purpose of choosing the provision of community reading parks is that to see from the reading interest of the Panduman community is very minimal, especially among adolescent and children communities. An example is the existence of TBM or community reading corner, based on socio-cultural values that are designed to know people's interest in reading by using an approach to the socio-cultural values of the communities where TBM is located. Purpose The implementation of community reading corner is intended to provide access to learning facilities that provide reading service, widespread and affordable by the community easily. Because community of reading corner has a role as a source of learning for young children, a source of information for parents in fostering early childhood, and recreational and educational facilities for the community.